Seizure burden and neuropsychological outcomes of new-onset refractory status epilepticus: Systematic review - Taraschenko, Olga; Pavuluri, Spriha; Schmidt, Cynthia M.; Pulluru, Yashwanth Reddy; Gupta, Navnika (Frontiers in Neurology, 2023)
Background Long-term sequelae of the new onset refractory status epilepticus (NORSE) include the development of epilepsy, cognitive deficits, and behavioral disturbances. The prevalence of these complications has been previously highlighted in case reports and case series: however, their full scope has not been comprehensively assessed. Methods We conducted a systematic review of the literature (PROSPERO ID CRD42022361142) regarding neurological and functional outcomes of NORSE at 30 days or longer following discharge from the hospital. A systematic review protocol was developed using guidance from the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results Of the 1,602 records for unique publications, 33 reports on adults and 52 reports on children met our inclusion criteria. They contained the description of 280 adults and 587 children of whom only 75.7 and 85% of patients, respectively had data on long-term follow-up. The mean age of adult and pediatric patients was 34.3 and 7.9 years, respectively; and the longest duration of follow up were 11 and 20 years, respectively. Seizure outcomes received major attention and were highlighted for 93.4 and 96.6% of the adult and pediatric NORSE patients, respectively. Seizures remained medically refractory in 41.1% of adults and 57.7% of children, while seizure freedom was achieved in only 26 and 23.3% of these patients, respectively. The long-term cognitive outcome data was provided for just 10.4% of the adult patients. In contrast, cognitive health data were supplied for 68.9% of the described children of whom 31.9% were moderately or severely disabled. Long-term functional outcomes assessed with various standardized scales were reported in 62.2 and 25.5% of the adults and children, respectively with majority of patients not being able to return to a pre-morbid level of functioning. New onset psychiatric disorders were reported in 3.3% of adults and 11.2% of children recovering from NORSE. Conclusion These findings concur with previous observations that the majority of adult and pediatric patients continue to experience recurrent seizures and suffer from refractory epilepsy. Moderate to severe cognitive disability, loss of functional independence, and psychiatric disorders represent a hallmark of chronic NORSE signifying the major public health importance of this disorder.